2022
DOI: 10.3389/fmed.2022.917019
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Challenge Causes Distinctive Symptomatic, Hemodynamic and Cognitive Responses in Long COVID and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: BackgroundSome patients with acute COVID-19 are left with persistent, debilitating fatigue, cognitive impairment (“brain fog”), orthostatic intolerance (OI) and other symptoms (“Long COVID”). Many of the symptoms are like those of other post-infectious fatigue syndromes and may meet criteria for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Common diagnostic laboratory tests are often unrevealing.MethodsWe evaluated whether a simple, standardized, office-based test of OI, the 10-min NASA Lean Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…Many researchers have commented on the similarity between ME/CFS and long COVID 99 ; around half of individuals with long COVID are estimated to meet the criteria for ME/CFS 10 , 11 , 29 , 100 , and in studies where the cardinal ME/CFS symptom of postexertional malaise is measured, a majority of individuals with long COVID report experiencing postexertional malaise 7 , 100 . A study of orthostatic stress in individuals with long COVID and individuals with ME/CFS found similar haemodynamic, symptomatic and cognitive abnormalities in both groups compared with healthy individuals 101 . Importantly, it is not surprising that ME/CFS should stem from SARS-CoV-2 infection as 27.1% of SARS-CoV infection survivors in one study met the criteria for ME/CFS diagnosis 4 years after onset 102 .…”
Section: Major Findingsmentioning
confidence: 91%
“…Many researchers have commented on the similarity between ME/CFS and long COVID 99 ; around half of individuals with long COVID are estimated to meet the criteria for ME/CFS 10 , 11 , 29 , 100 , and in studies where the cardinal ME/CFS symptom of postexertional malaise is measured, a majority of individuals with long COVID report experiencing postexertional malaise 7 , 100 . A study of orthostatic stress in individuals with long COVID and individuals with ME/CFS found similar haemodynamic, symptomatic and cognitive abnormalities in both groups compared with healthy individuals 101 . Importantly, it is not surprising that ME/CFS should stem from SARS-CoV-2 infection as 27.1% of SARS-CoV infection survivors in one study met the criteria for ME/CFS diagnosis 4 years after onset 102 .…”
Section: Major Findingsmentioning
confidence: 91%
“…Narrow PP has previously been reported as low in long covid patients during an NLT, 33 Vernon et al reported a significantly lower mean PP (20% of systolic BP at 10 min) compared to those with ME/CFS and the control group (29% of SBP at 10 min). There are studies suggesting an association between narrow PP and reduced cerebral blood flow in chronic fatigue patients 40,41 .…”
Section: Discussionmentioning
confidence: 86%
“…19,31,38 Whilst estimates of OH in long covid vary from 4% to 28%, our results are comparable to similarly-aged cohorts. 23,31 Some differences in estimated prevalence can be explained by different lean test protocols, for example, restricted diets, 33 which are not practical for routine clinic assessments. We applied commonly used criteria for PoTS, but implementation varies internationally.…”
Section: Additional Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A test reported recently [ 52 ] that can be performed even more simply in a clinician’s office is an orthostatic stress challenge that shows different symptomatic, hemodynamic, and cognitive abnormalities in people with Long COVID and ME/CFS, compared with healthy controls. Coupled to a smartphone app to assess cognition, it can provide objective confirmation of the orthostatic intolerance and brain fog reported by patients with Long COVID and ME/CFS.…”
Section: The Search For a Simple Universal Diagnostic Test For Me/cfsmentioning
confidence: 99%